2003
DOI: 10.1191/0961203303lu241cr
|View full text |Cite
|
Sign up to set email alerts
|

Bullous SLE: response to methotrexate and relationship with disease activity

Abstract: We report on a case of 40-year-old female with systemic lupus erythematosus (SLE) who developed a severe bullous eruption on sun-exposed areas. The bullous manifestation was associated with a flare of lupus serologies, whereas the previous manifestations of the disease were quiescent. Due to prior intolerance to many drugs, she was given oral methotrexate (10 mg/week). The drug administration was followed by a rapid and full resolution of cutaneous lesions. Five months later she developed a class III lupus nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 10 publications
0
27
1
5
Order By: Relevance
“…In this study, patients having bullous skin lesions had systemic flares that were also reported previously by Malcangi, et al . [21] An association between concomittant lupus nephritis and bullous lesions had been documented by Ng, et al [22] but no such association has been documented in this study.…”
Section: Discussioncontrasting
confidence: 43%
“…In this study, patients having bullous skin lesions had systemic flares that were also reported previously by Malcangi, et al . [21] An association between concomittant lupus nephritis and bullous lesions had been documented by Ng, et al [22] but no such association has been documented in this study.…”
Section: Discussioncontrasting
confidence: 43%
“…Type VII collagen is the major component of anchoring fibrils at the dermal-epidermal junction, and is the target of autoimmunity in patients with bullous SLE [19]. There has been at least one report of bullous eruption as the first clinical sign of SLE relapse [20] suggesting that skin damage can be a marker of disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…An association between BSLE and lupus nephritis is debated . In our literature review of pediatric BSLE cases, we found 21 of 33 (64%) cases that had renal involvement, and 12 of these (36%) were confirmed lupus nephritis.…”
Section: Discussionmentioning
confidence: 76%